Screening of Niger (Guizotia abyssinica) germplasm against sucking pests: Screening of Niger (Guizotia abyssinica) germplasm against sucking pests - SHIVALEELA; SUVARNA; SANGEETA; I MACHA (Journal of Oilseeds Research, 2023)
Studies were carried out on screening of 114 germplasm of Niger along with two check varieties RCR 18 and DNS 4 during kharif, 2020 at College of Agriculture, Raichur against sucking pests. Screening of Niger germplasms for their resistance or susceptibility against sucking pests viz., whiteflies, aphids and jassids based on the infestation. Among them 40 germplasm scored one (R), 36 germplasm scored two (MR), 22 germplasm scored three (MS), 12 germplasm scored four (HS) and 6 germplasm scored five(S)